Evolution of Blepharoplasty - Hicks, Katherine; Sclafani, Anthony P.; Thomas, James Regan (Facial Plastic Surgery, 2019)
The eyes and periorbital region are central components of facial beauty and harmony, but the periorbital region is also one of the earliest to show signs of aging. Over the past few decades, significant progress has been made in our understanding of the anatomy in this area, as well as the deleterious effects of aging in this region. In turn, surgical philosophy and techniques have evolved to better combat changes in this area to achieve a more youthful, natural appearance.
Keywords: upper blepharoplasty; lower blepharoplasty; surgical technique; history of blepharoplasty